2015
DOI: 10.1016/j.proenv.2015.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Curcumin and Pentagamavunon-0 Against Dengue-2 Virus Infection in Vero Cells; an in Vitro Study

Abstract: The research aims was to determine the cytotoxic effects and the highest safe concentration of curcumin and PGV-0 on vero cells. This research also compare the effect of curcumin and PGV-0 against vero cells infected by Dengue virus (in vitro) in one and three days incubation period. The highest safe concentrations against vero cells from curcumin was 6.25 ppm and 1.5625 ppm for PGV-0. Immunocytochemistry test of curcumin and PGV-0 in both incubation period (one and three days) shows no significant difference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The antiviral and antitumor effectiveness and safety of curcumin were also tested in vivo [42] [43]. Previous studies have investigated the effects of treating cells with curcumin on HSV-1 infection [35] or treating HSV-2 virions with curcumin [36]. This study is unique in investigating the effect on the infection cycle of curcumin-treated HSV-1 and HSV-2 virions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antiviral and antitumor effectiveness and safety of curcumin were also tested in vivo [42] [43]. Previous studies have investigated the effects of treating cells with curcumin on HSV-1 infection [35] or treating HSV-2 virions with curcumin [36]. This study is unique in investigating the effect on the infection cycle of curcumin-treated HSV-1 and HSV-2 virions.…”
Section: Discussionmentioning
confidence: 99%
“…This compound is demonstrated to contain antioxidant, anti-inflammatory, and antitumor properties [25]- [28]. Curcumin has also been demonstrated to have antiviral properties against hepatits B, hepatits C, influenza, enterovirus 71, and dengue virus [29]- [35]. Additionally, treatment of cells with curcumin has been demonstrated to inhibit immediate-early gene expression of HSV-1 [36].…”
Section: Introductionmentioning
confidence: 99%
“…Nanocurcumin improved cell uptake in comparison to curcumin [84,85]. Curcumin chitosan nanocomposite exhibited a better inhibition of entrance and replication of HCV in human hepatoma cells than curcumin [84].…”
Section: Formulation and Functional Improvement Of Curcuminmentioning
confidence: 92%
“…Curcumin and PGV-0 were tested for immunocytochemistry for both incubation periods (1 and 3 days) showed no remarkable changes and the Reverse transcriptase-Polymerase chain reaction test (RT-PCR) showed that the PGV -0 is more potent antiviral agent than curcumin. 19 Carneiro et al, 2017 investigated the molecular docking and characterisation of curcumin and monodimethylcurcumin ligands, as well as the dengue virus 5B1C protein (PDB code) (DENV-4). And these molecular docking results showed a correlation with the activity values of the compounds, which confirmed the importance of the residues for DENV-4 activity.…”
Section: Dengue Virusmentioning
confidence: 99%